ANALYSIS OF PREDICTIVE FACTORS OF MORTALITY IN HEMORRHAGIC STROKE PATIENTS AT SOEBANDI HOSPITAL JEMBER - Rida Darotin; Nurdiana Nurdiana; Tina Handayani Nasution (NurseLine Journal, 2017)
Stroke is a cerebrovascular disease that is often found in developed countries and currently also presents in developing countries, and one of them is in Indonesia. The high prevalence of stroke in Indonesia is affected by several risk factors such as obesity, lack of physical activity, unhealthy diet, smoking, high blood pressure, elevated blood sugar, and elevated blood lipid profile. The purpose of this study was to analyze the relationship between predictors of hemorrhagic stroke such as obesity, blood pressure, blood sugar and blood lipid profile with mortality in hemorrhagic stroke patients in RSD dr. Soebandi Jember. This research was a quantitative research with a retrospective approach. The number of samples was 101 medical record data. Univariate analysis was used to identify the description of each variable, a chi-square test was applied to analyze the correlation between variables, and the logistic regression analysis was applied to identify the most dominant factor influencing mortality of hemorrhagic stroke. The result of bivariate test showed p-value of obesity= 0,039, p-value of blood pressure= 0,478, p-value of blood sugar= 0,04, p-value of blood lipid profile= 0,026. Logistic regression obtained p-value for obesity= 0.043, OR = 2.689; p-value of blood sugar= 0,042, OR = 2,656; p-value of blood lipid profile= 0.069, OR = 3,749. There was a significant association between obesity, blood sugar, and blood lipid profile with mortality in hemorrhagic stroke patients. Obesity and blood sugar are predictors that can be used to predict mortality in hemorrhagic stroke patients, where obesity is the most dominant factor affecting mortality in hemorrhagic stroke patients.